Pengaruh Pendapatan dan Jumlah Anggota Keluarga Terhadap Kesejahteraan Keluarga di Kelurahan Karangasem - Ni Luh Ayu Utaminingsih; I Wayan Suwendra (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
The main purpose of this research was to determine the effect of income and number of family members on family welfare in Karangasem Village. This research is a type of causality research. The population of this research is the Head of Family in Karangasem Village with a sample of 374 families. The methods used for data collection were questionnaires and documentation. The data analysis technique used in this study was the t test and the F test to determine the effect of the independent variable on the dependent variable partially and simultaneously. The results showed that (1) income affects family welfare. This is indicated by the value of tcount = 5.498 > ttable = 1.966, (2) the number of family members affects family welfare. This is indicated by the value of tcount = 13.535 > ttable = 1.966, (3) income and the number of family members affects family welfare. This is indicated by the value of Fcount = 103,956 > Ftable = 3.02.